Transkulturowość czy glokalność? Dwa dyskursy o kondycji ponowoczesnej - Rewers, Ewa (Er(r)go. Teoria - Literatura - Kultura, 2003)
Ewa Rewers "Transculturalism or Glocalism? Two Discourses on the Postmodern Condition" Following Lotman's position on the necessary coexistence and overlapping of two or more languages, Rewers argues that multiculturalism is not just a cultural or social postulate but a basic, primordial situation of the postmodern world. Alongside global isation it has become a key notion, used to describe what Rewers calls the ground level in the study of culture. Further, she explores Florian Znaniecki's approach to cultural space and Ronald Robertson's notion of glocalisation as a global perspective adapted to local circumstances and conditions. Rewers singles out urban spaces as the most interesting areas for the study of cultural space. She puts forward a project of transcultural and transdisciplinary studies focused on urban space, which should become part of what she describes as critical cultural studies.